Kebijakan Pemberian Vonis Mati Atau Pidana Mati Yang Ada di dalam Kitab Undang Undang Hukum Pidana Ditinjau Dari Formulasi Perspektif Pembaharuan Undang-Undang No 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Putri, Ina Malia; Rahmatiar, Yuniar; Abas, Muhamad (Wajah Hukum, 2023)
Capital punishment is a compelling and expansive type of discipline, and the discussion about the upsides and downsides of the death penalty go on today. The question of whether the death penalty should be retained in the Criminal Code or abolished in the justice system is inseparable from Indonesia's reform of criminal law, particularly through the creation of the Criminal Code. Despite the fact that its nature differs from that outlined in the Criminal Code, Indonesia will continue to use the death penalty, as evidenced by the Criminal Code Bill, which contains the death penalty. The purpose of this research is to identify the current legal formulation of death penalty policies in Indonesian criminal law and to examine the desired future legal formulation of death penalty policies in Indonesia. This study utilizes a subjective technique with a legitimate and administrative methodology as well as unmistakable scientific exploration details. According to the findings of this study, the death penalty is still regulated by Indonesian law as the primary form of punishment, resulting in disagreements between pro- and anti-death penalty groups. In the new version of Indonesian criminal law, change in death penalty policy, originally a principal punishment to become an alternative punishment . In the future, the death penalty will be a tangible expression of human rights that is in line with national and international perspectives.